Knowledge on and use of the FORTA (“Fit fOR The Aged”)-list and the FORTA App by general practitioners in Baden-Württemberg, Germany - Meyer, Liesbeth; Wehling, Martin (European geriatric medicine, 2020)
To identify the knowledge on and use of the FORTA (“Fit fOR The Aged”)-list and FORTA App in Baden-Württemberg, Germany.